Specifications of material and labor required for the erection and completion of a public art gallery - Bull, Elmer A. (My University, 1908)
Introduction: The specifications and drawings are to be construed in their full meaning and intent, whether taken separately or together. They are deemed to explain each other and to be sufficiently descriptive of the necessary work to be performed under the contract.
Citation: Bull, Elmer A. Specifications of material and labor required for the erection and completion of a public art gallery. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Architecture; Blueprints; Construction; Art Galleries; Graduating theses; Senior theses; Theses